(untitled) (Bangladesh Journal of Pharmacology, 2025)
This study aimed to examine the effect of 1α,25-dihydroxyvitamin D3 [1,25(OH)2D3] on the intracellular persistence of uropathogenic Escherichia coli. After establishing a cell infection model and conducting drug intervention, methods such as fluorescent probes, Western blot, and qPCR were used. The results showed that 1,25(OH)2D3 (10 nM) reduced the number of persistent E. coli (at 12 and 24 hours) (P<0.05), enhanced the acidification of intracellular lysosomes (p<0.05), and up-regulated the expression levels of transcription factor binding to IGHM enhancer 3, ATPase H+ transporting V0 subunit C, and ATPase H+ transporting V0 subunit D2 (P<0.05). Therefore, 1,25(OH)2D3 may reduce bacterial persistence by enhancing lysosomal acidification and influencing the expression of these factors. These findings provide ideas for the potential application of 1,25(OH)2D3 in reducing the recurrence rate of infectious diseases.